OPERAS: bringing the long tail of Social Sciences and Humanities into Open Science - Giglia, Elena (Septentrio Conference Series, 2018)
Watch the VIDEO. The talk will present OPERAS, a comprehensive infrastructure aimed at providing a pan-European infrastructure to rethink and reshape publishing, discovery and dissemination addressing the specificity and the critical issues of Social Sciences and Humanities (SSH). OPERAS’ aim is to meet the specific needs of SSH scholars in an open environment, taking care of all the steps of the scholarly communication cycle. OPERAS’ unique approach is to unite researchers, libraries and publishers in a common effort, in order to take back control over scholarly communication. Not merging nor replacing, but nurturing existing realities, OPERAS provides innovative services to bring SSH into Open Science. OPERAS is designed to elaborate effective and scalable long-term strategies for the future development of the digital infrastructure and community building needed to innovate scholarly communication in the SSH. OPERAS’ pervading idea of science as communication holds an immense potential for an inspiring model of Open Science with direct societal impact, based on continuous communication.